PENJAMINAN MUTU: PENERAPAN, PEMENUHAN, DAN PENGENDALIAN STANDAR MUTU SERTA IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN - APRIYANTI WIDIANSYAH (Universitas Bina Sarana Informatika, 2019)
The study was conducted to determine the application, fulfillment, and control of quality standards and their implementation in the world of education. Qualitative methods are used with Descriptive Research types. The results and discussion of efforts to maintain the quality of education are difficult to release in relation to quality management. In quality management all management functions carried out by education managers are directed so that all services provided to the maximum extent possible or exceed customer expectations. In connection with these efforts, efforts are needed to control quality or quality control. In the perspective of quality management, controlling the quality of a product after it is produced can face the risk of a number of products that do not meet the expected standards. This means that the production process is more expensive. In the field of education this logic also applies. Keywords: Implementation, Quality Assurance, Education